ANALISIS KEBIJAKAN HUTAN RAKYAT KEMITRAAN YANG BERKELANJUTAN - Mahawan Karuniasa; Niken Probo Laras (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2021)
Private forest partnership has been considered as a new strategy in dealing with conventional socio-economic model problem of the industrial wood raw material sustainability supply. As a new strategy to address the issue of sustainability of industrial wood supply, synergy is needed between forest farmer groups and timber-based industry through private forest partnership schemes. This research aims to analyze private forest partnership policy and its implementation in terms of cooperation aspects in order to formulate a sustainable private forest partnership policy. Content analysis was used to identify all policies related to private forestry partnerships, while policy implementation was analyzed by using formal evaluation method. The descriptive method was implemented to analyze standing stock managemet, and Analytical Hierarchy Process (AHP) as a method to formulate the concept of sustainable private forest partnership policy. The results showed that private forest partnership policy now is more focused on production facilities and infrastructure aspect. The level of policy implementation in research location is at a low grade, only reached 16.28%, while 43.75% of the private forest partnerships in the research area are not sustainable due to low potential of standing stock. This research proved that fostering the farmers is a key factor to develop sustainable private forest partnership policy.